Penerapan Flipped Classroom Learning Terhadap Motivasi Olahraga dan Hasil Belajar Siswa pada Ekstrakurikuler Basket SMPN 44 Bandung - Muhammad Fathurrahman; Yusuf Hidayat; Sufyar Mudjianto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to determine the effect of implementing the flipped classroom learning model on students' motivation toward physical education and their learning outcomes in the basketball extracurricular activity at SMPN 44 Bandung. This study employed an experimental method using a quasi-experimental approach and a pretest-posttest control group design. The study sample consisted of 32 students divided into two groups using the stratified random assignment technique, resulting in 16 students in each group: the experimental group (n = 16) and the control group (n = 16). The instruments used were the Sport Motivation Scale-II (SMS-II) to measure sports motivation and second-semester final exam report card scores to measure student learning outcomes. The results showed that, in general, the implementation of the Flipped Classroom Learning model did not have a significant effect on sports motivation (p = 0.273) or learning outcomes (p = 0.255). However, analysis based on the SMS-II subscales revealed a significant effect on external regulation (p = 0.005). The conclusion of this study is that the Flipped Classroom Learning model, with a 6-week intervention, did not have a significant effect on students' sports motivation and learning outcomes, but was effective in reducing students' external regulation in the basketball extracurricular program at SMPN 44 Bandung. Keywords: Basketball Extracurricular Program, Flipped Classroom Learning, Learning Outcomes, Sports Motivation, Self-Determination Theory